The Effectiveness Of Receivables Control Through The Analysis Of Days Sales Out-standing (Dso) At Pt Xxx - Destriviani, Viola; Rusaktiva Rustam, Akie (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This descriptive qualitative study aims to analyze accounts receivable management at PT XXX, a company providing operational services and workforce management for various industrial projects, in 2024, using the Days Sales Outstanding (DSO) indicator. The study focuses on the main issues affecting DSO fluctuations and the effectiveness of receivables management. Data were obtained through interviews with employees of the Controller and Operations departments and from an analysis of the 2024 audited financial statements. The findings indicate that DSO fluctuations were caused by internal factors, namely differences in billing mechanisms and lengthy administrative processes, as well as external factors, including delays in documentation from clients, multi-level validation procedures, and low levels of digitalization on the client side. Although PT XXX has implemented a 90-day Service Level Agreement (SLA), an AR-tracking system, and routine coordination, the effectiveness of receivables management remains limited due to its dependence on the speed of client validation. Overall, receivables management at PT XXX has not yet been optimal, indicating the need for improved coordination and administrative simplification to support smoother cash flow.